THE QUALITY OF HEALTH SERVICE FOR ELDERLY PATIENTS : BETWEEN EXPECTATIONS AND REALITY - Amirul Mustofa; Rinawati Rinawati (Universitas Muhammadiyah Sidoarjo, 2020)
The development of the elderly population in the city of Surabaya continues to increase in line with the population growth rate. Naturally, the elderly people experience a biological aging process that has an impact on their health. Therefore, health care for the elderly is an urgent problem to find a solution. This study aims to analyze health services for elderly patients using five dimensions of quality service and to analyze the various expectations of elderly patients on the health services received. The method of research is carried out with a qualitative approach. Data were collected by conducting interviews with several specialist doctors, service officers, elderly patients as service recipients. Interviews were carried out by snowballing in the sense that the researchers conducted rolling interviews from one research subject to another, in order to obtain data that was in accordance with the target focus of the study. The results show, first: of the five dimensions of service, there are four dimensions of service that are in the good evaluation criteria, except for the responsiveness dimension. Second, the services provided are not in accordance with the expectations of service recipients, because health services for elderly patients have not been implemented independently. Various health service facilities have been provided, elderly patients cannot enjoy it comfortably and safely, because they are still mixed with general patients.